A colheita e a acolhida do inesperado : para uma mitopoética do cotidiano - Carvalho, Marcos de (2008)
In this study, the objective was to foment mythically and poetically the discussions about the quotidian of men and women. Filled with a particular knowledge of the myth and poetry, we tried to create, in the interface of several oposite pairs on which the metaphisic thought had designed the world, new connections, new intercommunications and interactions possibilities. All this effort is directed, on the first and last instance, in order to propose a new design for the school quotidian. A reorganization that goes through the break of a millenar structure that had lead the human being to the highest in skills and tecnology, but, on the other hand, had put him so far from the possibility of building a human and fair society.